Pectus excavactum-insights into its diagnosis and the current treatment options along with its clinical outcomes: two case reports - Iroegbu, Chukwuemeka D.; Zhongxi, Zhou; Sheng, Tan; Jiang, B. O.; Jingsong, Liu (International Surgery Journal, 2018)
Pectus excavatum (PE) is a congenital sternal depression, one of the most frequent major congenital malformations of the chest wall. Generally, the malformation is not associated with functional disorders and often constitutes an aesthetic alteration with significant psychological distress. Nevertheless, the surgical repair of PE in childhood has been a well-established procedure with modified Ravitch repair (MRR) and minimally invasive repair (MIR) by Nuss been the two most popular methods of corrections. As a means of concealing the ugly skin scars caused by the MRR technique, the procedure was however highly modified with the use of bilateral inframammarian separated skin incisions. However, MIR has been a preferable technique due to its shorter operative time and minimal blood loss, but its postoperative complications have so far seemed to be its limiting factor whereas, extensive and combined deformities of the ventral chest wall are classically corrected using either MIR by Nuss and the MRR technique. Notwithstanding, Conservative treatment using alloplastic implants or vacuum bell to elevate the sternum in patients with mild PE defect is becoming a potential alternative and a means of preventing unnecessary surgical procedures mostly in mild funnel chest. Presented here is a case of PE surgical correction in a 12-year-old boy and an 11-year-old girl with pectus bar dislodgment. This article analyses the chain of events between both patients, reviews the literature on the subject and other currently available treatment options.